Intramural spatial variation of optical tissue properties measured with fluorescence microsphere images of porcine cardiac tissue - Goyal, A; Van Den Wijngaard, J; Van Horssen, P; Grau, V; Spaan, J; Smitha, N (2009)
This proceeding studies the optical fluorescence images of a porcine heart filled with microspheres of two colors, carmine and red. A significant difference in the total optical tissue attenuation coefficient was observed between excitation and emission for both carmine (excitation - 13±4(1/mm) and emission - 9.4±3(1/mm)) and red (excitation - 29±5(1/mm) and emission - 25±5(1/mm)), indicating that optical tissue properties can change significantly for a small change in light wavelength. The above-mentioned large ranges of variation observed in the tissue attenuation coefficient for excitation and emission (both for carmine and red) suggest significant intramural variation of optical properties across the entire organ. Patterns of global spatial variation in optical attenuation properties in tissue across the entire organ were observed. A novel method using fluorescence microsphere images is presented for measurement of the tissue attenuation's intramural variation across an entire organ. ©2009 IEEE.